Capillary-Induced Wrinkle-to-Fold Transitions Under Biaxial Compression - Nagashima, So; Nakatani, Akihiro (Langmuir, 2021)
Wrinkles in bilayer systems comprising a thin stiff film attached to a soft substrate can globally transition into folds under sufficiently large compression. This phenomenon has been extensively studied primarily using uniaxially compressed systems. However, inducing the wrinkle-to-fold transition at designated locations on a wrinkled surface under small biaxial compression remains a challenge. In this study, we describe a method for causing randomly oriented wrinkles to locally evolve into folds using water droplets. When a droplet comes into contact with the random wrinkles that have spontaneously formed upon film deposition owing to residual biaxial compressive strains, radially extended folds instantaneously emerge at the droplet boundary. Upon water evaporation, the wrinkles beneath the droplet also undergo a transition, leaving a fold network. By contrast, the surface regions distant from where the droplet was placed retain the wrinkle morphology. The folded areas can be controlled by adjusting the volume and number of droplets. These transitions are enabled by the capillary forces of water that help to increase the local compressive strains. This capillary-induced wrinkle-to-fold transition provides a simple mechanism to develop folds in selected locations on wrinkled surfaces of film–substrate systems subject to small biaxial compression, which is unachievable with conventional approaches.